Change and Moral Development in Kant’s Ethics - Curran, Kyle (Stance: an international undergraduate philosophy journal, 2013)
This paper is concerned with an ambiguous aspect of Kant’s ethics, namely, how moral change is possible. Kant conceives that change is possible, indeed desirable, without making clear the mechanism by which this change occurs. I conclude that one’s moral development must come about through the autonomous rationality of humanity. This allows for the moral law to be held at all times and for the rejection of immoral sentiments and inclinations. Further, it is constant soulsearching that allows one to keep a check on their maxims, facilitating the development of a moral disposition.